Apart from the Medical Complaints, Why do Patients Use Emergency Medical Services? Results of a Patient Survey - Piedmont, Silke; Reinhold, Anna Katharina; Bock, Jens-Oliver; Rothhardt, Janett; Swart, Enno; Robra, Bernt-Peter (Das Gesundheitswesen, 2021)
Introduction Many countries face an increased use of emergency medical services (EMS) with a decreasing percentage of life-threatening complaints. Though there is a broad discussion among experts about the cause, patients' self-perceived, non-medical reasons for using EMS remain largely unknown.Methods The written survey included EMS patients who had≥1 case of prehospital emergency care in 2016. Four German health insurance companies sent out postal questionnaires to 1312 insured patients. The response rate was 20%; 254 questionnaires were eligible for descriptive and interferential analyses (t-tests, chi2-tests, logistic models).Results The majority of respondents indicated that their EMS use was due to an emergency or someone else’s decision (≥84%; multiple checks allowed); 56% gave need for a quick transport as a reason. Other frequently stated reasons addressed the health care system (e. g., complaints outside of physicians’ opening hours) and insecurity/anxiety about one’s state of health (>45% of the respondents). “Social factors” were similarly important (e. g., 42% affirming, “No one could give me a ride to the emergency department or doctor’s office.”). Every fifth person had contact with other emergency care providers prior to EMS use. Respondents negating an emergency as a reason were less likely to confirm wanting immediate medical care on site or quick transports compared to those affirming an emergency. Patients using EMS at night more often denied having an emergency compared to patients with access to care during the day.Conclusion The study identified a bundle of reasons leading to EMS use apart from medical complaints. Attempts for needs-oriented EMS use should essentially include optimization of the health care and social support system and measures to reduce patients’ insecurity.
Keywords: ambulance; emergency medical services; patients; prehospital emergency care; surveys and questionnaires